Imágenes concretas como estrategia metodológica para propiciar la producción oral (2019)
"Improving the oral expression of students and the understanding and interpretation of different types of oral messages" has always been one of the primary objectives of language teaching in school; however, rarely the uses and forms of oral communication became the object of a systematized teaching, which took into account the differences between spoken language and written language, as two different kinds of communication from the same linguistic system . Oral language, unlike writing, is undoubtedly extracurricular learning. The school concentrates its attention on the formal learning of the written language, because it is its unavoidable responsibility (and, often, it puts so much zeal in the fulfillment of this commitment that it leaves in the forgetfulness, during the process of teaching of the reading-writing, the knowledge that children have acquired, before and outside of it, about the writing system and the written language). En la Institución Educativa Técnica Industrial San Antonio de Padua, del municipio de Soledad, los estudiantes presentan falencias en los procesos de aprendizaje, en lectura y escritura, y en especial en el desempeño oral, lo cual es reflejado en lengua castellana y por ende en las demás áreas del saber; evidenciándose más claramente en los resultados arrojados por las pruebas de estado (pruebas saber). At Institución Educativa Técnica Industrial San Antonio de Padua, in Soledad, students present flaws in the learning processes, in reading and writing, and especially in oral performance, which is reflected in the Spanish language and therefore in the other areas of knowledge; evidencing more clearly in the results thrown by the state tests (SABER tests). For this reason, this research will be carried out in order to promote oral production in fourth grade students of primary school, using concrete images as a methodological strategy to achieve this goal. This research project is framed in the curriculum line, will be managed with a qualitative approach, and approaches the object of knowledge from the case study, using an inductive research method, and longitudinal cutting. The population is of a finite nature made up of fourth grade students. With this research proposal, students are expected to improve their performances in oral production through the implementation of activities (workshops) in which the concrete images are used and each of the objectives set is achieved. Likewise, this proposal is feasible as it has the support and support of the institutional units.